Creative twists in the tale: Narrative and visual methodologies in action - Bradbury, Jill (PINS-Psychology in Society, 2017)
Narrative methodologies emphasise the temporal quality of both lived lives and told stories, and enable us to attend to the ways in which the grand narratives of history and socio-political life articulate with individual, personal lives or psychological realities. However, the narrative approach entails three key epistemological and/or political problems: 1) the imposition of a particular conception of a “good” narrative (and by implication, psyche or life) that entails logical flow, integration and coherence; 2) the production and re-inscription of a gap between life and story, particularly stories told in research interviews; and 3) individualising single narrators extracted from their contexts. I argue that combining narrative research methods with visual methodologies within an action research paradigm may assist us to work through and against these limitations. Visual methodologies are relatively commonplace as a means to collect data, particularly helpful when stories are difficult to articulate. I suggest extending the use of visual techniques to facilitate creative representation and productive analysis. Examples of innovative visual representations of data illustrate possibilities for challenging the limits above: 1) Repetitive stress injuries: Non-stories and visual techniques for sense-making; 2) Visual tracking of multiple temporal trajectories; and 3) Re-invoking the relational quality of narrated identity.